The Shift of Sentencing Paradigm from Retributive to Restorative Justice in the Indonesian Criminal Justice System - Carolina S. Martha; Angga Aldilla Gusman; Ainurrafiqa Pelupessy (PT. Anagata Sembagi Education, 2026)
The development of modern criminal law thought indicates a significant shift in the sentencing paradigm from a retributive approach toward a restorative one. The retributive paradigm, which emphasizes punishment and retaliation for criminal acts, has increasingly been criticized for its inability to deliver substantive justice for victims, offenders, and society. In contrast, restorative justice emerges as an alternative paradigm that prioritizes restoration, dialogue, and the active participation of all parties affected by crime. This article aims to analyze the shift in sentencing paradigm from retributive to restorative justice within the Indonesian criminal justice system and to examine its implications for national criminal law reform. This study employs a qualitative legal research method using normative and conceptual approaches, relying on statutory analysis, legal doctrines, and relevant criminal justice policies. The findings reveal that restorative justice has gained increasing recognition in Indonesia through recent regulations and law enforcement policies. However, its implementation still faces substantial challenges in terms of legal substance, institutional structure, and legal culture. The novelty of this article lies in its comprehensive analysis of restorative justice not merely as an alternative mechanism, but as a potential new sentencing paradigm capable of reshaping the core orientation of Indonesian criminal law.